2010
DOI: 10.4161/psb.5.6.11777
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of SOS1 deficiency

Abstract: As much as there is known about the function of the sodium/proton antiporter SOS1 in plants, recent studies point towards a more general role for this protein. The crucial involvement in salt stress protection is clearly one of its functions -confined to the N-terminus, but the modular structure of the protein includes a segment with several domains that are functionally not studied but comprise more than half of the protein's length. Additional functions of the protein appear to be an influence on vesicle tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The expression differences of some the K + , Na + and Ca + transporters between GsSOS1 mutant and wild type were also observed, Some of the K + channel protein-coding genes SKOR and AKT1, sodium/calcium exchanger, sodium transporter HKT1, as well as 11 other intracellular traffic-related genes (Supplementary File 3). In Arabidopsis SOS1 mutant, expression of CNGC19 gene, encoding a calmodulin-binding cyclic nucleotide-gated channel, is strongly upregulated (Oh et al, 2010b). In this study, the alteration in the expression levels of four CNGC genes in GsSOS1 mutant roots was also detected.…”
Section: The Function Prediction Of the Degs Affected By The Gene Mutmentioning
confidence: 53%
See 2 more Smart Citations
“…The expression differences of some the K + , Na + and Ca + transporters between GsSOS1 mutant and wild type were also observed, Some of the K + channel protein-coding genes SKOR and AKT1, sodium/calcium exchanger, sodium transporter HKT1, as well as 11 other intracellular traffic-related genes (Supplementary File 3). In Arabidopsis SOS1 mutant, expression of CNGC19 gene, encoding a calmodulin-binding cyclic nucleotide-gated channel, is strongly upregulated (Oh et al, 2010b). In this study, the alteration in the expression levels of four CNGC genes in GsSOS1 mutant roots was also detected.…”
Section: The Function Prediction Of the Degs Affected By The Gene Mutmentioning
confidence: 53%
“…In addition, KEGG analysis of DEGs in GsSOS1 mutant roots showed that GsSOS1 mutation significantly influenced the expression of many other genes that involved in different pathway, including hormone signal transduction, phenylpropanoid biosynthesis, starch-sucrose metabolism, circadian rhythm and plant-pathogen interactions ( Figure A4). Earlier, a few of the reports also suggest biological functions that are affected in SOS1 mutants of Arabidopsis, includes plants pathogen responses and circadian rhythm (Oh et al, 2010b). Hence, it is highly likely that the SOS1 is involved in more than one functions such as those observed in the current study.…”
Section: The Function Prediction Of the Degs Affected By The Gene Mutmentioning
confidence: 59%
See 1 more Smart Citation
“…In dividing microspores of orchids, an MT array named generative pole MT system (GPMS) was observed between the plasma membrane and the prophase microspore nucleus prior to the assembly of the spindle (Brown and Lemmon, 1991). However, this MT array was not observed in dividing microspores expressing a green fluorescent protein (GFP)-tubulin marker in A. thaliana and tobacco (Oh et al, 2010a,c). Instead a perinuclear MT network extends to the cell cortex (Oh et al, 2010c).…”
mentioning
confidence: 99%
“…In A. thaliana , immunolocalization of MTs in intact pollen grains was recently made possible (Lee et al, 2007). Moreover, a microgametophyte specific GFP-tubulin marker was introduced in tobacco and A. thaliana , so that transgenic microgametophytes are ready for the observation of MT arrays in live cells (Oh et al, 2010a,c). …”
mentioning
confidence: 99%